Simple, Inexpensive Procedure for the Disruption of Bacteria - Ranhand, Jon M. (1974)
Small volumes (1 to 2 ml) of bacterial cultures, with turbidities ranging from 3 to 10, were disrupted 50 to 90% (measured as a decrease in turbidity) within 2 min, by shaking them on a Vortex-type mixer in the presence of glass beads. This method of disrupton was effective for cells in the following genera: Streptococcus, Lactobacillus, Staphylococcus, Bacillus, and Escherichia. After low-speed centrifugation, the resulting extract can be used as potential sources for enzymes, transforming deoxyribonucleic acids, cell walls, membranes, etc.